Pembinaan dan Pengembangan Produk Hasil Pertanian melalui Metode Packaging Modern - Epriyandi, Epriyandi; Helanianto, Helanianto; Polonia, Betti Ses Eka; Rahmadi, Hairian; Yusuf, Yusuf; Marjuki, Ismael; Anhar, Muh; Ruchiyat, Asep; Nurmayasari, Dewi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Local farmers in Sungai Awan Kanan Village are one of the supporting sources of food for consumers around Ketapang Regency, West Kalimantan. With traditional skills they are able to produce agricultural products that can compete with modern agriculture. They always produce fresh vegetables every day for family and community needs. Behind it all, there are several weaknesses that they currently feel, including; cheap prices at the collector level (prices become a game for certain parties), fresh vegetables cannot last long due to limited supporting facilities. Meanwhile, on the other hand, there are opportunities that actually open the chain of their problems, such as; the emergence of supermarkets and modern markets that require supplies. The aim of implementing this community service is to encourage the strength of local communities in developing agricultural products, especially vegetables, through packaging methods. The community is facilitated by providing modern packaging for the agricultural products they get. With this community service program in the form of training regarding the development of agricultural products through packaging, it is hoped that it can increase public knowledge about how to increase income through packaging methods applied to agricultural products. After the training, almost all training participants realized that the packaging methods applied to agricultural products could have a good effect on the sales of their agricultural products.